KUS121, a VCP modulator, attenuates ischemic retinal cell death via suppressing endoplasmic reticulum stress - Hata, Masayuki (Sci Rep, 2017)
Ischemic neural damages cause several devastating diseases, including brain stroke and ischemic retinopathies, and endoplasmic reticulum (ER) stress has been proposed to be the underlying mechanism of the neuronal cell death of these conditions. We previously synthesized Kyoto University substances (KUSs) as modulators of valosin-containing protein (VCP); KUSs inhibit VCP ATPase activity and protect cells from different cell death-inducing insults. Here, we examined the efficacy of KUS121 in a rat model of retinal ischemic injury. Systemic administration of KUS121 to rats with ischemic retinal injury significantly suppressed inner retinal thinning and death of retinal ganglion and amacrine cells, with a significant functional maintenance of visual functions, as judged by electroretinography. Furthermore, intravitreal injection of KUS121, which is the clinically preferred route of drug administration for retinal diseases, appeared to show an equal or better neuroprotective efficacy in the ischemic retina compared with systemic administration. Indeed, induction of the ER stress marker C/EBP homologous protein (CHOP) after the ischemic insult was significantly suppressed by KUS121 administration. Our study suggests VCP modulation by KUS as a promising novel therapeutic strategy for ischemic neuronal diseases.